Growth of CNTs on 304 stainless steel using sparked iron as a catalyst - Thongtem S. (2014)
Carbon nanotubes (CNTs) were grown on 304 stainless steel using iron as a catalyst. By using the applied voltages of 4-6 kV, iron wire with 0.5 mm in diameter was sparked for 1, 2, 10 and 100 times to form catalytic dots on the steel substrate. CNTs were subsequently grown in a gas mixture of 10 ml/s Ar and 0.1 ml/s C2H2 at a temperature range 700 - 900 K for 300 s (5 min). The dots and CNTs were characterised using AFM, SEM and TEM to determine their characteristics.